EJAAN BAHASA BALI DENGAN HURUF LATIN (EYD BALI LATIN) - I Ketut Ngurah Sulibra; Ni Ketut Ratna Ekawati (Journal Social and Humaniora, 2017)
Abstract: This spelling came into e?ect after the government established the EyD of Indonesian language in 1972. The purpose of enacting EyD Bali Latin was in order to standardize Balinese language without losing the distinctiveness of Balinese language. The EyD is based on a Latin alphabet of 26 pieces. Some consonants such as / f /, / kh /, / q /, / sy /, / v /, / z /, / x / are used to write foreign vocabulary uptake. To write the Kawi-Latin spelling (Kawi-Latin literary pair), especially in writing Old Kawi / Javanese vocabulary in relation to the script alphabet from the Balinese script to Latin script can be used guidance of Ancient Java Dictionary in accordance with consonant classification or script script. Keywords: standardization, spelling, vowels, consonants, pairs of literature